Annual Time Series of Air Temperature, Precipitation, and Urban Area Extent in Modena, Italy - Stefano Orlandini (PANGAEA, 2023)
An uninterrupted data set of 139 annual values of local mean air temperature T, cumulative precipitation depth P, urban area extent A, global mean surface air temperature G, and global CO2 concentration C for the 1881-2019 period of time is shared with the scientific community. The annual time series of T and P are obtained from daily observations collected at the Geophysical Observatory of the University of Modena and Reggio Emilia, Modena, Italy. Observations of A for the town of Modena are available for years 1881, 1940, 1961, 1971, 1981, 1998, 2000, and 2002–2019. Cubic spline interpolation is applied to obtain reconstructed values of A for the other years in the 1881-2019 period of time. The annual time series of G is obtained by adding the NASA GISTEMP temperature change to the average temperature observed in Modena in the 1951–1980 base period so that it can be meaningfully compared to the observed local temperature T. Global CO2 concentration C estimated from ice cores, from 1881 to 1958, and observed in the Mauna Loa Observatory, Hawaii, from 1959 to 2019, are combined to provide the annual time series of C for the 1881-2019 period of time. Matlab code performing a nonlinear analysis of the data and resulting PDF files containing scatter plots are also shared with the scientific community.